KEGIATAN - KEGIATAN YANG MEMERLUKAN IZIN DI KOTA SEMARANG - Dwi Poernomo (Faculty of Law, Universitas Diponegoro, 2011)
Licensing is one of tools of policy to drive the development. Then it can be used to set permissions for permits contain restrictions and conditions. Viewed from the applicant perspective,licensing should be able to provide protection.